The effect of verotoxin producing escherichia coli in development of experimental gastroenteritis among streptomycin treated murine model: a longitudinal study - Mosharraf, Fahareen Binta; Ahsan, Chowdhury Rafiqul; Nessa, Jamalun; Yasmin, Mahmuda (© 2013 Bangladesh Journal of Microbiology, 2016)
This article was published in the Bangladesh Journal of Microbiology and Development [© 2013] and The Journal's website is at:http://www.banglajol.info/index.php/BJM/article/view/28450